1998
DOI: 10.1103/physrevb.58.14548
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram of optimally dopedYBa2Cu3O7

Abstract: Influence of the oxygen stoichiometry on the phase diagram of clean YBa 2 Cu 3 O 7Ϫ␦ single crystals has been studied in the region of optimal doping (0.05Ͻ␦Ͻ0.09). Temperature and angular dependencies of magnetoresistance were analyzed for fields of up to 23 T. At low fields a sharp resistivity kink, which is a signature of the first order melting transition, was observed in all the samples studied. This kink, however, disappears when B exceeds the multicritical field B mc . It was found that B mc strongly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…[17][18][19] With raising ␦ in the region near optimal doping due to the increase in the density of oxygen vacancies, pinning disorder is enhanced whereas at the same time the elastic energy remains almost unchanged. 10 Consequently, as predicted in Refs. 17-19, a shift of the location of the B pl (T) line to lower field values should take place in agreement with our observations.…”
Section: B Phase Diagramsupporting
confidence: 60%
See 1 more Smart Citation
“…[17][18][19] With raising ␦ in the region near optimal doping due to the increase in the density of oxygen vacancies, pinning disorder is enhanced whereas at the same time the elastic energy remains almost unchanged. 10 Consequently, as predicted in Refs. 17-19, a shift of the location of the B pl (T) line to lower field values should take place in agreement with our observations.…”
Section: B Phase Diagramsupporting
confidence: 60%
“…2 Indeed, such a melting transition has been observed in numerous experiments with a variety of techniques, and for clean samples has been established to be of the first order. [3][4][5][6][7][8][9][10] The mixed state in the phase diagram of the HTSC becomes even more complicated if one considers the presence of quenched disorder and its interplay with thermal fluctuations. As shown long ago the Abrikosov lattice is unstable to point disorder beyond the Larkin length.…”
Section: Introductionmentioning
confidence: 99%
“…Large thermal energy would help overcome the effects of pinning centers in both cases, however, the FC state being more (macroscopically) uniform eventually produces a better ordered FLL with a larger correlation volume V c of the Larkin domain (than that in the ZFC case). We note that Kokkaliaris et al [18] have recently reported that in an untwinned YBCO crystal, which displays the phenomenon of a broad second magnetization peak (to be designated as H s p ) at high fields and lower temperatures,…”
Section: History Effects In χ′(T ) Behaviormentioning
confidence: 72%
“…The detailed characteristics of the evolution of the anomalous variation in J c across the (H,T) region of the second magnetization peak and that of the conventional peak effect are far from being understood in the context of a variety of HTSC systems [14][15][16][17][18]. In contrast, in the conventional low T c superconductors (LTSC) with considerably smaller (but often not negligible) thermal fluctuations, a PE near the normal state boundary (H c2 line) is a common occurrence over the entire field-temperature regime [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in the oxygen content has three major effects: first there are changes in the density of current carriers leading to a modification in the onset of the transition temperature (T c ) and magnetic penetration depth [2]. The second effect is that oxygen depletion increases the number of point defects [3]. Also the anisotropy of the YBCO crystal can be controlled by the oxygen content, weakening the coupling between Cu±O layers, driving the system more two dimensionally [4 to 6].…”
mentioning
confidence: 99%